Analysis of Financial Statements of Micro, Small and Medium Enterprises (Umkm) Cafe Aceh Meutuah Khupie, Percut Sei Tuan District, Deli Serdang Using the Standard Approach to Financial Accounting for Micro, Small and Medium Entities (Sakemkm) - Dharma, Budi; Sari Harahap, Epa Purnama; Maulida, Syakya (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are companies with a single owner, manager, and a limited number of capital investors. In this study, descriptive qualitative research is used. gathering information or data for research through observation and interviews. According to studies done through interviews, Cafe Aceh Meutuah Khupie did not adhere to Micro, Small, and Medium Entity Accounting Standards and only kept financial records of its sales, purchases of raw materials, staff compensation costs, and other costs (SAK EMKM).